2021
DOI: 10.1371/journal.pone.0253709
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuation of oral anticoagulation therapy after successful atrial fibrillation ablation: A systematic review and meta-analysis of prospective studies

Abstract: Background The safety of discontinuing oral anticoagulant (OAC) therapy after atrial fibrillation (AF) ablation remains controversial. A meta-analysis was performed to assess the safety and feasibility of discontinuing OAC therapy after successful AF ablation. Methods PubMed and Embase were searched up to October 2020 for prospective cohort studies that reported the risk of thromboembolism (TE) after successful AF ablation in off-OAC and on-OAC groups. The primary outcome was the incidence of TE events. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
(133 reference statements)
0
3
1
Order By: Relevance
“…Despite the fact that several studies have suggested a positive correlation between AF burden and stroke risk [20], there has remained an ongoing debate about OAC discontinuation following successful catheter ablation over the last decade. Nevertheless, existing data on this issue have been limited to observational studies and remained controversial [21][22][23][24][25][26]. In this present study, while we found no significant association between OAC discontinuation and clinical adverse events, we could not exclude that the finding was likely underpowered due to the small number of events.…”
Section: Discussioncontrasting
confidence: 74%
“…Despite the fact that several studies have suggested a positive correlation between AF burden and stroke risk [20], there has remained an ongoing debate about OAC discontinuation following successful catheter ablation over the last decade. Nevertheless, existing data on this issue have been limited to observational studies and remained controversial [21][22][23][24][25][26]. In this present study, while we found no significant association between OAC discontinuation and clinical adverse events, we could not exclude that the finding was likely underpowered due to the small number of events.…”
Section: Discussioncontrasting
confidence: 74%
“…Previous meta-analyses have found similar results. [ 32 , 33 ] Compared with the published articles, we conducted stratified analysis by the risk of stroke to determine the exact incidence rate of TE in different risk level groups, and we included all cohort studies meeting inclusion criteria to expand the sample while eliminating the study of patients who discontinued OACs within 3 months after ablation. All we did can make the results more stable and credible to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…The cessation of OAC post catheter ablation has been well studied. A meta-analysis by Liu et al demonstrated a similar cumulative thromboembolic rate on and off OAC post ablation of 1.1% and 1.4% respectively [ 28 ]. Additionally, the rate of haemorrhagic complications in the group off OAC was significantly lower [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis by Liu et al demonstrated a similar cumulative thromboembolic rate on and off OAC post ablation of 1.1% and 1.4% respectively [ 28 ]. Additionally, the rate of haemorrhagic complications in the group off OAC was significantly lower [ 28 ]. Convergent ablation hafs a higher FFAF than catheter ablation alone, expectedly the cessation of OAC would be higher in these cohorts.…”
Section: Discussionmentioning
confidence: 99%